2014
DOI: 10.1111/pops.12208
|View full text |Cite
|
Sign up to set email alerts
|

Increased Complexity Has Its Benefits

Abstract: This piece is a response to the Conway, Conway, Gornick, and Houck (2014) description of an automated method for assessing integrative complexity. It builds on the authors' 15 years of experience in automating a variety of textual analysis coding schemes including that measuring conceptual complexity and is intended to address some of the issues raised in the process of automating content analysis categories.KEY WORDS: integrative complexity, conceptual complexity, automated content analysis Conway and his ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Scores can be compared for test‐retest and interscorer reliability, and they can be subjected to standard statistical analyses. Conceptual complexity theory, with its idea of trait complexity as increasing across differentiation and integration, also underlies Conway, Conway, Gornick, and Houck's () and Young and Hermann's () computerized approaches to cognitive complexity scoring, which are described in the current symposium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scores can be compared for test‐retest and interscorer reliability, and they can be subjected to standard statistical analyses. Conceptual complexity theory, with its idea of trait complexity as increasing across differentiation and integration, also underlies Conway, Conway, Gornick, and Houck's () and Young and Hermann's () computerized approaches to cognitive complexity scoring, which are described in the current symposium.…”
mentioning
confidence: 99%
“…Both Conway et al. 's () and Young and Hermann's () automated approaches are foundations on which closer approximations of human scoring can be built. In fact, the current versions of both appear more promising than previous ones.…”
mentioning
confidence: 99%
“…But, as Conway et al. () show, even the best correlations between human IC codes and automated IC codes are only moderate—and even these values almost certainly understate the divergence (e.g., large correlations between two sets of codes can comfortably coexist with poor agreement between sets, as pointed out by Young & Hermann [] and with large mean differences between scores from one set and from another set).…”
Section: Identifying Errors and The Elusive Quest For A Gold Standardmentioning
confidence: 99%
“…Our colleagues Young and Hermann () have suggested that a multipass system can help ameliorate these difficulties, for instance, by coding different parts of speech differently. We also see potential in multipass systems, potential to incorporate more fine‐tuned distinctions between word senses and indications of sentiments.…”
Section: The Future Of Algorithmsmentioning
confidence: 99%
“…Automating integrative complexity is fraught with many challenges. We would first like to express our sincere gratitude to Suedfeld and Tetlock (), Tetlock, Metz, Scott, and Suedfeld (), and Young and Hermann () for tackling some of these challenges. Their contributions in this symposium spur an important dialogue about the current state of automating complexity and its future possibilities.…”
mentioning
confidence: 99%